Determinants of Diabetic Peripheral Neuropathy and Their Clinical Significance: A Retrospective Cohort Study - Cheng, Yifan; Cao, Wen; Zhang, Junzhe; Wang, Jiabin; Liu, Xiang; Wu, Qianqian; Lin, Qingxia (Frontiers in Endocrinology, 2022)
Background In this study, we investigated the epidemiological characteristics and predictors of diabetic peripheral neuropathy (DPN) in adult patients with type 2 diabetes mellitus (DM). Methods The study was designed as a retrospective cohort trial at the First Affiliated Hospital of Wenzhou Medical University. From January 2017 to December 2020, a total of 1,262 patients with DM were enrolled to assess the risk factors for DPN. The patients were divided into two groups (DPN group and non-DPN group). The Mann–Whitney U test or t-test, receiver operating characteristic (ROC) analyses, univariate chi-square analyses, and multiple logistic regression analyses were used to analyze the adjusted predictors of DPN. Results The overall prevalence of DPN in DM patients was 72.7% (n = 793/1,091). Multivariate analysis revealed that age > 66 years (odds ratio [OR], 2.647; 95% confidence interval [CI] 1.469–4.770; p = 0.002), history of hypertension (OR, 1.829; 95% CI 1.146–2.920; p = 0.011), neutrophil (NE) levels exceeding 4.0 × 109/L (OR 0.256; 95% CI 0.162–0.405; p = 0.001), lymphocyte (LY) levels over 3.0 × 109/L (OR 7.173; 95% CI 4.258–12.086; p = 0.000), HbA1c > 7.7% (OR 3.151; 95% CI 1.959–5.068; p = 0.000), and FT3 > 4.4 pmol/L (OR 0.417; 95% CI 0.263–0.662; p = 0.000) were six significant predictive factors for the prevalence of DPN. Conclusions High levels of LY, HbA1c, history of hypertension, and > 66 years of age increase the risk of DPN in adult patients with DM, while high levels of NE and FT3 were protective factors of DPN. Thus, the prediction of DPN can significantly be improved by identifying older patients over the age of 66 and history of hypertension, as well as establishing the biochemical cutoff values of NE, LY, HbA1c, and FT3.